2020
DOI: 10.1021/acsmacrolett.0c00175
|View full text |Cite
|
Sign up to set email alerts
|

Photopatternable, Branched Polymer Hydrogels Based on Linear Macromonomers for 3D Cell Culture Applications

Abstract: Photochemical ligation strategies in hydrogel materials are crucial to model spatiotemporal phenomena that occur in the natural extracellular matrix. We here describe the use of cyclic 1,2-dithiolanes to cross-link with norbornene on linear poly­(ethylene glycol) polymers through UV irradiation in a rapid and byproduct-free manner, resulting in branched macromolecular architectures and hydrogel materials from low-viscosity precursor solutions. Oscillatory rheology and NMR data indicate the one-pot formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Although the disulfide bond is relatively strong (with a bond dissociation energy of roughly 60 kcal/mol), many disulfides are susceptible to cleavage by electrophiles, nucleophiles, reducing agents, free radicals, and even directly by specific wavelengths of light. The unique chemistry surrounding disulfides has resulted in a recent surge of the incorporation of disulfides into polymeric systems. Polymers containing disulfides have been used for: stress relaxation, self-healing adaptable networks, controlled drug release, chain-transfer agents, increase of refractive index through the introduction of sulfur atoms, latent protection of thiols, and ring-opening polymerizations of 1,2-dithiolanes and 1,2-dithianes. , …”
Section: Introductionmentioning
confidence: 99%
“…Although the disulfide bond is relatively strong (with a bond dissociation energy of roughly 60 kcal/mol), many disulfides are susceptible to cleavage by electrophiles, nucleophiles, reducing agents, free radicals, and even directly by specific wavelengths of light. The unique chemistry surrounding disulfides has resulted in a recent surge of the incorporation of disulfides into polymeric systems. Polymers containing disulfides have been used for: stress relaxation, self-healing adaptable networks, controlled drug release, chain-transfer agents, increase of refractive index through the introduction of sulfur atoms, latent protection of thiols, and ring-opening polymerizations of 1,2-dithiolanes and 1,2-dithianes. , …”
Section: Introductionmentioning
confidence: 99%
“…UV irradiation-induced cross-linking of DT is likely responsible for the abrupt increase in hydrogel stiffness; the ring opening of the DT moiety with light in the multicomponent squaramide-based supramolecular materials was confirmed by solid-state NMR experiments against a covalent polymer PEGdiDT control ( Figures S13 and S14 ). 54 …”
Section: Results and Discussionmentioning
confidence: 99%
“…We further explored the possibility for spatiotemporal patterning of bioactive cues in supramolecular materials to mimic the heterogeneity of tissues in vivo. Fluorescent ( (fluorescein)GK(DT)GGGRGDS 54 and non-fluorescent ( (DT)GGGRGDS ( DT-RGD )) RGD peptides with a DT moiety were synthesized to enable photopatterning using either a photomask or direct laser writing (DLW) ( Figure 6 A). The efficiency of binding of the RGD peptide to SQ/10SQ-DT hydrogel by UV irradiation was found to be around 20% for samples of different RGD concentrations ( Figure S31 ), after homogenous UV exposure using a benchtop LED (5 min, ∼10 mW/cm 2 , 375 nm).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The self-healing, biocompatibility, photocontrolled viscoelastic properties, as well as gel-to-sol transition, make these hydrogels interesting for release of a molecular cargo in the presence of living cells. Tong and co-workers reported that UV irradiation of DT- and norbornene (NB)-terminated PEG in the presence of LAP led to production of a hydrogel containing reversible dynamic S–S as well as irreversible thioether bonds . Light irradiation and ring opening of DT produced thiyl radicals, which could be added to the disulfide and double bonds of DT or NB to form reversible and irreversible cross-links, respectively.…”
Section: Light-responsive Homolytically Cleavable Dynamic Covalent Bondsmentioning
confidence: 99%